Efficacy of immunization with a recombinant S. aureus vaccine formulated with liposomes and ODN-CpG against natural S. aureus intramammary infections in heifers and cows. (July 2022) - Camussone, C.M.; Reidel, I.G.; Molineri, A.I.; Cicotello, J.; Miotti, C.; Suarez Archilla, G.A.; Curti, C.C.; Veaute, C.; Calvinho, L.F.
Abstract: The aims of the present study were to evaluate the ability of a subunit vaccine composed of recombinant molecules of α-toxin, β-toxin, FnBPA and ClfA, formulated with cationic liposomes and CpG-ODN, to confer protection against natural S. aureus intramammary infection (IMI) and to assess the antibody response against the vaccine components. A stringent criterion based on molecular identification of the isolates was used to define IMI. The proportion of animals that developed new S. aureus IMI was higher in the Control group compared with the Vaccine group (reduction of 60.7%), and time to new S. aureus IMI was higher for animals in the Vaccine group compared with animals in the Control group, although not statistically significant. Molecular identification of the isolates allowed the detection of S. aureus pulsotypes that appeared transiently in milk and others that were able to establish IMI, providing a new perspective to define parameters related to the definition of new IMI and cures. Specific IgG, IgG1 and IgG2 levels against the four recombinant proteins included in the vaccine were significantly increased in the vaccinated group and the recombinant α-toxin included in the vaccine generated antibodies that reduced significantly the haemolytic activity of native α-toxin. Data reported in the present study indicate a possible effect on both the proportion of animals developing new IMI and the time to new S. aureus IMI, but the incidence of disease within the study was too low to provide statistical confirmation. Highlights: Vaccination led to a 60.7% reduction in new S. aureus IMI compared to control group, although not statistically significant. Time to new S. aureus IMI higher for animals in the Vaccine group in comparison to animals in the Control group, although not statistically significant. Molecular identification of the isolates allowed differentiation of PT causing transient and persistent IMI. Antibody levels against the four vaccine antigens were significantly higher in the vaccinated group during the study period. Recombinant α-toxin included in the vaccine generated antibodies that reduced the haemolytic activity of native α-toxin.